The breeding system and reproductive ecology of the endangered plant Fagopyrum dibotrys (D. Don) Hara - Chen, Ming-Lin; You, Ya-Li; Wen, Hui-Hui; Li, Ying (Bangladesh Journal of Botany, 2015)
Distyly has been confirmed in Fagopyrum dibotrys (D. Don) Hara. The species are dimorphic in style length, anther height, pollen size and number but not in flower diameter, pollen surface ornamentation and stigma papilla cells. In F. dibotrys populations, style-morph ratios vary from isoplethy (1L : 1S) to strongly L-biased, or they more often contain only the L-morph. Moreover, it was found that larger isoplethic populations of F. dibotrys could produce more seeds than smaller single-morph populations. F. dibotrys had a smaller population size, morph-biased populations, and lower seed setting, which could be the reasons for the decrease in its population DOI: http://dx.doi.org/10.3329/bjb.v43i2.21673 Bangladesh J. Bot. 43(2): 197-205, 2014 (September)